Influence of electrolytic parameters in the formation of TiO2 nanotubes over Ti6Al4V. (2020) - Poddar, Shashank; Bit, Arindam; Sinha, Sudip Kumar
Abstract: Metallic biomaterials are widely used in the orthopaedic research field for bone fixation, prosthetic device as well as in dental applications. Titanium-based alloys are considered a suitable candidate for implant-based applications because of its specific material property. Among various materials explored, Ti6Al4V is a promising material which has been widely used for implant applications. Surface property of these alloys plays a major role in most of the applications. In this regard, modification of the surface by nanodesigning has been utilized to improve the surface properties of the titanium and its alloys for biomedical application. However, certain parameters are needed to control the surface morphology of the alloy. Thus, in order to get titania (TiO2 ) nanotubes arrays over the Ti6Al4V alloy different electrolytes has been used. In the present study, Ethylene glycol (EG) and Ethylene glycol and Distilled water (EGDW) with ammonium fluoride salt were used as electrolytes. Voltage was kept constant in both the electrolytes. Moreover, diameter of the formed nanotubes was found to be changed when anodization was done in two different electrolytes. Inner and outer diameter of the as-synthesized nanotubes when anodization carried out in ethylene glycol was found to be 43.3571 nm and 93.6288 nm respectively. Whereas inner and outer diameter of as developed nanotubes when anodizing was carried out in Ethylene glycol and Distilled water (EGDW) was found to be 33.8484 nm and 89.9901 nm respectively. Moreover, as-synthesized anodized samples were heat-treated at 450 °C for 3 h. The prepared samples were characterized by scanning electron microscopy and XRD to study the phase change and the tube diameter in the developed nanostructure.